2004
DOI: 10.1109/tbme.2004.827936
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Characterization of Firing Dynamics of Spontaneous Bursts in Cultured Neural Networks

Abstract: Extracellular action potentials were recorded from developing dissociated rat neocortical networks continuously for up to 49 days in vitro using planar multielectrode arrays. Spontaneous neuronal activity emerged toward the end of the first week in vitro and from then on exhibited periods of elevated firing rates, lasting for a few days up to weeks, which were largely uncorrelated among different recording sites. On a time scale of seconds to minutes, network activity typically displayed an ongoing repetition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
237
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(261 citation statements)
references
References 53 publications
18
237
0
6
Order By: Relevance
“…5AB). In agreement with previous studies (Kamioka et al, 1996;van Pelt et al, 2004), we observed that the spontaneous spikes became synchronized bursts during the development of neuronal networks (Fig. 5B).…”
Section: Electrical Activity Recordingssupporting
confidence: 93%
See 1 more Smart Citation
“…5AB). In agreement with previous studies (Kamioka et al, 1996;van Pelt et al, 2004), we observed that the spontaneous spikes became synchronized bursts during the development of neuronal networks (Fig. 5B).…”
Section: Electrical Activity Recordingssupporting
confidence: 93%
“…However, these previous studies focused mainly on early synaptic formation during early network construction. Network activity is known to show a mature pattern of synchronized bursting after random spontaneous activity in long-term culture (Kamioka et al, 1996;van Pelt et al, 2004;Chiappalone et al, 2006;Wagenaar et al, 2006). During this long-term development, however, how sufficient synaptic connections are established and how the density becomes saturated remain unclear.…”
mentioning
confidence: 99%
“…Unlike simulated neural networks where the initial state and network configuration can be controlled, an LCN exhibits complicated spontaneous dynamics (Rolston et al, 2007;Segev et al, 2004;Wagenaar et al, 2006) whose activity patterns evolve over the course of development in vitro (van Pelt et al, 2004). These dynamics typically consist of episodes of increasing spontaneous asynchronous action potentials that culminate in a synchronous population burst of activity followed by a quiescent period.…”
Section: Inputmentioning
confidence: 99%
“…Complex networks of neurons can be cultured in vitro and kept alive and physiologically active for years at a time. Multiple distinct spatiotemporal oscillatory patterns emerge spontaneously in these chronic neural cultures [160,161,166]. Populations of neurons attached to a multi-electrode array can be connected to tissue-engineered axons that are free to integrate with a host nerve stump upon transplantation [69,112].…”
Section: Ectopic Neural Modulesmentioning
confidence: 99%